2020
DOI: 10.1177/0954406220909853
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization design for the blade angles of hydraulic torque converter with adjustable pump

Abstract: To improve the efficiency of a hydraulic torque converter with adjustable pump at low load and thus increase the operation scope of high efficiency, multi-objective optimization design is carried out for the blade angles by incorporating three-dimensional steady computational fluid dynamics numerical simulation, design of experiments, Kriging surrogate model and multi-objective genetic algorithm. The results show that the angle of blade trailing edge in first-stage stator is the main influencing factor of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Due to the complexity of the working fluid flow within the HTC, it is not possible to numerically solve without certain simplifications and assumptions. Below are some simplifications and assumptions made for the computational model of the HTC [13].…”
Section: Computational Modelmentioning
confidence: 99%
“…Due to the complexity of the working fluid flow within the HTC, it is not possible to numerically solve without certain simplifications and assumptions. Below are some simplifications and assumptions made for the computational model of the HTC [13].…”
Section: Computational Modelmentioning
confidence: 99%
“…Surrogate-based optimization as an advantageous tool for research and development goals has been practical in various aspects of turbomachinery design and performance evaluation. [28][29][30][31][32][33] For instance, optimization of centrifugal fans for ventilating applications has been widely considered in several researches. [34][35][36] In Table 1, details of some related papers on the surrogate-based optimization of turbomachinery components are listed.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 With the gradual maturity of numerical simulation technology, some studies use numerical simulation to analyse the transient and steady-state flow fields of HTC. 48 Scholars found that steady-state calculations cannot calculate the transient characteristics and cannot correctly predict the true flow of fluids. 9,10 However, the three-dimensional transient full channel model can be used to better predict the true flow state of fluid.…”
Section: Introductionmentioning
confidence: 99%